The effect of intensive statin therapy in non-symptomatic intracranial arteries: The STAMINA-MRI sub-study - Sim, Jae Eun; Song, Ha-Na; Choi, Jong-Un; Lee, Ji-Eun; Baek, In Young; Cho, Hwan-Ho; Kim, Jong-Hoon; Chung, Jong-Won; Kim, Gyeong-Moon; Park, Hyun-Jin; Bang, Oh Young; Seo, Woo-Keun (Frontiers in Neurology, 2023)
Background and aims: Pleiotropic effects of statins result in stabilization of symptomatic intracranial arterial plaque. However, little is known about the effect of statins in non-symptomatic cerebral arteries. We hypothesized that intensive statin therapy could produce a change in the non-symptomatic cerebral arteries. Methods: This is a sub-study of a prospective observational study under the title of the Intensive Statin Treatment in Acute Ischemic Stroke patients with Intracranial Atherosclerosis: a High-Resolution Magnetic Resonance Imaging (HR-MRI) study. Patients with statin-naïve acute ischemic stroke who had symptomatic intracranial artery stenosis (above 50%) were recruited for this study. HR-MRI was performed to assess the patients’ cerebral arterial status before and 6 months after statin therapy. To demonstrate the effect of statins in the non-symptomatic segment of intracranial cerebral arteries, we excluded symptomatic segments from the data to be analyzed. We compared the morphological changes using cerebrovascular morphometry. Results: 54 patients (mean age: 62.9 ± 14.4 years, 59.3% women) were included in this study. Intensive statin therapy produced significant morphologic changes spread over overall. Among the morphological features, the arterial luminal area showed the highest number of significant changes with a range of 5.7% and 6.7%. Systolic blood pressure (SBP) was an independent factor associated with relative changes in posterior circulation bed maximal diameter % change (beta -0.21, 95% confidence interval -0.36 - -0.07, p = 0.005). Conclusions: Intensive statin therapy produced a favorable morphological change in cerebral arteries of not only the target arterial segment but also in non-symptomatic arterial segments. The change in cerebral arterial luminal diameter was influenced by the baseline SBP and was dependent on the topographic distribution of the cerebral arteries.